2005
DOI: 10.1002/hep.20918
|View full text |Cite
|
Sign up to set email alerts
|

Oral adeno-associated virus-sTRAIL gene therapy suppresses human hepatocellular carcinoma growth in mice

Abstract: T umor necrosis factor-related apoptosis-inducing ligand (TRAIL) is a type II transmembrane protein. Both membrane-bound and soluble forms of TRAIL selectively trigger apoptosis in tumor cells but not in most normal cells in vivo. 1,2 Many attempts have been made to study the therapeutic potential of TRAIL in cancer gene therapy in the last decade. It has been demonstrated recently that TRAIL or TRAIL-green fluorescent protein fusion gene expression mediated by adenoviral vectors results in apoptosis and bysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 21 publications
2
32
0
Order By: Relevance
“…It is reported that histidinetagged TRAIL has an altered protein conformation, reduced stability, decreased solubility, and liver toxicity; however, the soluble form of native TRAIL without tags is able to kill cancer cells with little or no evidence of toxicity to primary human hepatocytes in vitro (34). We previously proved that the recombinant soluble form of native TRAIL (rsTRAIL) produced in our laboratory was safe both in vivo and in vitro (14,17,26). In the present study, we observed that W peptide -enhanced endogenous TRAIL expression suppressed the growth of transplanted mouse liver tumor cells without toxicity to lung, liver, spleen, and kidney (data no shown).…”
Section: Discussionmentioning
confidence: 93%
“…It is reported that histidinetagged TRAIL has an altered protein conformation, reduced stability, decreased solubility, and liver toxicity; however, the soluble form of native TRAIL without tags is able to kill cancer cells with little or no evidence of toxicity to primary human hepatocytes in vitro (34). We previously proved that the recombinant soluble form of native TRAIL (rsTRAIL) produced in our laboratory was safe both in vivo and in vitro (14,17,26). In the present study, we observed that W peptide -enhanced endogenous TRAIL expression suppressed the growth of transplanted mouse liver tumor cells without toxicity to lung, liver, spleen, and kidney (data no shown).…”
Section: Discussionmentioning
confidence: 93%
“…More interestingly, we demonstrated that oral or intraperitoneal administration of rAAV-TRAIL resulted in an effective suppression of tumor growth without toxicity to normal hepatocytes since AAV is more resistant to acid and alkali, suggesting that oral administration of rAAV-TRAIL might be an important alternative route with practical significance for cancer gene therapy. 26 Yoo et al 34 also reported that intratumor injection of rAAV2 encoding soluble TRAIL to A549 lung adenocarcinoma mouse models (s.c.) led to 62% of reduced tumor size, and systemic delivery before implantation of A549 cells lowered the frequency of tumor occurrence to 43%, compared to 100% in untreated mice. These data strongly suggest that it is possible to increase AAV-mediated sTRAIL expression as a novel therapeutic strategy for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that the rAAV2-sTRAIL virus infection significantly suppressed tumor growth and prolonged survival of mice implanted with human liver cancer or leukemia, while toxicity to normal tissue and cells was undetectable. 25,26 To further evaluate the safety and potential use in clinical trials for cancer, validation and safety test were carried out in this study. , and the expression of sTRAIL reached the peak at MOI of 2 × 10 5 vg per cell.…”
Section: Soluble Trail Expression and Bioactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Intratumoral administration of the TRAIL vector by electroporation significantly inhibited the growth not only of the HCC directly administered TRAIL vector, but also of distant subcutaneous HCC, with only small and transient liver damage being observed [57]. More interestingly, Ma et al recently demonstrated that adeno-associated virus (AAV) vector expressing the extracellular domain of TRAIL fused with a signal peptide could be administered orally or intraperitoneally, resulting in long-term and high level expression of soluble TRAIL in vivo, effective regression of the subcutaneously implanted tumors, and lack of toxicity to normal hepatocytes [58]. It will be interesting to further test whether such systemic administration of TRAIL exerts similar tumoricidal effects on orthotopic liver tumors.…”
Section: Apoptosis-mediated Cell Deathmentioning
confidence: 99%